Prophecy, history and method: how and why Isaac Newton studied chronology - Schilt, C (2018)
Isaac Newton spent forty years of his life studying the chronology of ancient civilizations. The manuscript record that bears the fruits of these writings is in significant disarray, which has led to many misinformed conclusions about the nature of his research and his motivations for studying the topic in the first place. By devoting ample attention to Newton’s reading, note-taking, writing, and ordering practices, this thesis makes use both of evidence drawn from Newton's surviving books and of Newton’s digitised manuscripts and transcriptions to reconstruct the evolution of his chronological writings. Originally just an eight-page treatise on the origins of idolatry, ‘Theologiae Gentilis Origines Philosphicae’ (mid-1680s), Newton started expanding and revising it to eventually arrive at the posthumously published Chronology of Ancient Kingdoms Amended (1728). I show that most of the writings he composed in the interval were all part of a single treatise, the ‘Originals’ (1702–06), in which he built on his original research. In truth, Newton’s chronological studies began even before the ‘Origines’, with his studies of the prophecies in the books of Daniel and Revelation. In order to correctly identify the four monarchies from Daniel and their role in past, present, and future, he needed a reliable timeframe. From Greek and Roman sources he derived a timeline of the kings that reigned over Babylon during the Jewish Exile, which he subsequently collated with the Scriptural record, not shunning to amend the chronological books of Ezra and Nehemiah where necessary. With the ‘‘Origines’’ and ‘Originals’, Newton constructed a timeframe from Greek history using methods from genealogy and astronomy that allowed him to incorporate all of sacred and profane history. Posthumous editorial projects and the scattered manuscript record have obscured much of the connections between Newton’s chronological and prophetic writings, yet for Newton they were part of one and the same project.